Implementation of a surgical ward innovation: Telemonitoring controlled by healthdot [SWITCH-trial PROTOCOL] - Friso Schonck; Misha Luyer; Nardo van der Meer; Arthur Bouwman; Simon Nienhuijs (PLoS ONE, 2025)
Background Monitoring patients’ vital signs is important to detect abnormalities that may indicate a disturbed postoperative course. However, manual monitoring or so-called spot checks performed by nursing staff require a significant amount and are time-consuming. Wearable devices have been shown to be at least equally effective in collecting these data and have the possibility for continuous monitoring. This technology could enhance improvements in early warning score systems by continuous measurement or ease onward monitoring after earlier discharge. Furthermore, the implementation of wearables for patient monitoring may also decrease the workload for nursing staff. However, it is still unclear how workload is impacted after the implementation of continuous monitoring by wearables in a surgical ward. Methods The level of workload for nursing staff will be assessed by the Integrated Workload Scale [IWS] in an observational study on the stepwise implementation of continuous monitoring at a surgical ward. In a 6-month period, the vital parameters of 500 oncological surgery patients will be recorded using an accelerometer [Healthdot ® Philips] which measures heart rate and respiration rate, gradually leaving out spot checks by nurses. Proctor et al.’s taxonomy of implementation outcomes is used to guide other outcomes: acceptability, appropriateness, feasibility, adoption, penetration, implementation cost and sustainability. Measurements will be performed by device performances of signal noise ratio and [suspected] adverse events, questionnaires Evidence Based Practice Attitude [EBPAS] and System Usability Scale [SUS] and a focus group information that will be processed and objectified by means of a Braun and Clarke thematic analysis. Discussion Implementation is complex, especially within healthcare. While the validity of monitoring devices has been studied, their implementation in daily practice has been explored to a limited extent. This study focuses on implementation, with nurses as the primary research group. Aim The aim is to investigate the implementation of continuous monitoring using a wearable device regarding efficiency and workload primarily on nursing perspective. Trial registration ClinicalTrials.gov NCT05956210, Registered on 21 July 2023